Is the Number of Missing Teeth Associated With Mortality? A Longitudinal Study Using a National Health Screening Cohort - Kim, So Young; Lee, Chang Ho; Yoo, Dae Myoung; Kwon, Mi Jung; Kim, Ji Hee; Kim, Joo-Hee; Byun, Soo-Hwan; Park, Bumjung; Lee, Hyo-Jeong; Choi, Hyo Geun (Frontiers in Medicine, 2022)
This study aimed to estimate the risk of mortality related to the number of missing teeth in a South Korean population. The ≥ 40-year-old population of the Korean National Health Insurance Service-Health Screening Cohort 2002–2003 was analyzed. Participants were selected from a total of 220,189 participants and included in groups of 0 teeth lost, 1–2 teeth lost, and ≥ 3 teeth lost. Among the total population, 17,211 participants were included in no missing teeth, 1–2 missing teeth, and ≥ 3 missing teeth and were randomly matched 1:1:1 for age and sex. Mortality from specific causes and all-cause mortality were compared among the groups. The hazard ratio (HR) of the number of missing teeth for all-cause mortality or each cause of mortality was analyzed using Cox proportional hazard models. According to the cause of death, the HRs for metabolic disease, digestive disease, and trauma were greater in the group with ≥ 3 missing teeth than in the no missing teeth group. The group with ≥ 3 missing teeth indicated a 1.19-fold higher HR for all-cause mortality than the no missing teeth group [95% confidence intervals (95% CIs) = 1.12–1.27, P < 0.001]. The group with 1- 2 missing teeth did not show a higher HR for all-cause mortality. In the group with 1–2 missing teeth, the HRs for mortality from mental disease and digestive disease were higher than those in the no missing teeth group. The group with 1–2 missing teeth did not show a higher HR for all-cause mortality. The number of missing teeth was linked with a higher risk of mortality. For specific causes of mortality, mortality from metabolic disease, digestive disease, and trauma was higher in the participants with the number of missing teeth.